Application of Murabahah Agreement in Griya Purchase Financing at BSI Sub Branch Office Gatsu Denpasar - R Agrosamdhyo (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Bank Syariah Indonesia has been providing Islamic financial products and services, including murabahah agreement, in order to cater to the growing demand for Sharia-compliant financing options. One of the key areas where murabahah agreement is applied is in the financing for purchasing homes, known as Griya Purchase Financing. Griya purchase Financing is one of the financing companies owned by BSI KCP Gatsu Denpasar. However, this financing often encounters problems in the purchase process. The aims of this study are: to find out the factors that lead to a murabahah contract in the financing of a purchase griya at BSI KCP Gatsu Denpasar and to find out the process of financing the griya purchase at BSI KCP Gatsu Denpasar. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The data analysis technique used is the Miles and Huberman model, which includes data collection, data reduction, data presentation, and data verification. data validity technique with the triangulation technique. The results of the study found: 1) There are factors that cause a murabaha contract to occur, namely the presence of the object of the contract; 2) The murabaha contract process by submitting asset documents to the consumer as a sign of consent qabul with the consumer. And financing for purchase houses that are free from usury in accordance with the Fatwa of the National Sharia Council, MUI No.04/DSN-MUI/IV/2000, dated April 1, 2000, conceming murabahha.; 3) The process of financing purchase housing includes BSI having the terms and benefits of financing purchase housing. To attract consumer, as well as with light installments, one of the benefits of purchase financing at BSI is that consumers still feel able to meet other needs.